THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION (AT PT ICI PAINTS INDONESIA) - Muhammad Ali Iqbal; Ahmad Badawi Saluy; Asep Yusuf Hamdani (Dinasti International Journal of Education Management And Social Science, 2021)
The effect of work motivation and work environment on employee performance is mediated by job satisfaction (at PT. Ici Paint Indonesia). The research used is descriptive analysis and causality of the population. The respondents of this research were 105 population samples, this analysis method used path analysis, coefficients, and inter-dimensional analysis. The results here show (H1) Work motivation has a positive and significant effect on job satisfaction, (H2) Work environment on job satisfaction has a positive and significant effect, (H3) Work motivation on employee performance has a positive and significant effect, (H4) Work environment on employee performance positive and significant effect, (H5) Job satisfaction on employee performance has a positive and significant effect, (H6) Work motivation on performance through job satisfaction has a positive and significant effect, (H7) the work environment on employee performance through job satisfaction has a positive and significant effect. The independent variable (x) is work motivation (x1) and work environment (x2). The dependent variable is job satisfaction (y1) and performance (y2), from the research it is proven from the hypothesis that has been researched and calculated through the Spss 23 application.